Epigenetic changes in the metabolically healthy obese: A case-control versus a prospective study - Linares-Pineda, Teresa María; Boughanem Lakhal, Hatim; Gutiérrez Repiso, Carolina; Macías-González, Manuel; Andrés-León, Eduardo; Rojo-Martínez, Gemma; Valdés, Sergio (Wiley, 2022)
Obesity has become a worldwide health problem, in which latest statistics reported an increased trend over the last years. Accordingly, long-term obesity is involved in an increased risk of developing several metabolic diseases, such as cardiovascular diseases, insulin resistance or type 2 diabetes. Although it is common to find obesity-related disorders in the majority of individuals with obesity, some of them do not show metabolic complications.1 Obese people without these metabolic disorders are defined as metabolically healthy obesity (MHO) individuals, whereas those who present metabolic complications are known as metabolically unhealthy obesity (MUO) subjects.2 Importantly, the prevalence of this healthy phenotype varies widely, in which a correct diagnosis is critical for a good prognosis.2, 3 Nevertheless, the variability of this prevalence may be due to the nature of related-study designs and the studied populations or the confounding variables considered. Therefore, conducting appropriately designed studies to evaluate important clinical research questions is crucial, to elucidate the impact of MHO in the progression of detrimental obesity-related phenotypes.4 In this case, epigenetic arises as a valuable tool for clinical applications. Epigenetic mechanisms might be implicated in the regulation of several metabolic disorders.5 However, until now, only a few studies have been conducted to understand the epigenetic changes in individuals with MHO and MUO.6-8 Therefore, we hypothesized that epigenetic changes may be involved in the development and the transition from MHO to MUO phenotype. Consequently, the aim of this study was to analyze the epigenome-wide DNA methylation study in peripheral blood mononuclear cells (PMBCs) from participants with MHO and MUO, by using two study designs, such as case-control and prospective approaches.
Keywords: Obesidad; Health problem; Obesity; Metabolic diseases